Evaluación a la cartera de crédito para minimizar la morosidad de los saldos, en la cooperativa Minga Ltda., período 2018 - Wendy Lizeth, Guanga Guanga (2021)
The credit union Minga Ltda., seeks to improve the quality of life of its associates and when observing that there is a high percentage of overdue portfolio, it was necessary to carry out this research project entitled evaluation of the portfolio to minimize the delinquency of balances in the credit union Minga Ltda., corresponding to the year 2018, in order to reduce the delinquency in their balances. It was based on the determination of the problem, which led to the definition of the objectives. Clear definitions were included in the state of the art, the methodology was based on the deductive and inductive method; the level of research was considered descriptive, field and bibliographic, with a qualitative and quantitative approach, and was considered non-experimental. The results of the evaluation of the loan portfolio led to the lack of an evaluation of this item and the process of granting loans, there is a high rate of overdue portfolio which causes a low profitability in the institution, that is why strategies and the respective conclusions and recommendations are proposed focused on the results obtained for an improvement in the portfolio, in the process of granting loans and in the entity.